SAT0086 Rapid Access Rheumatology Consultation (RAC) – an Office-Based Pilot Project. (10th June 2014) - Puchner, R.; Kaiser, W.; Tremetsberger, R.; Steininger, M.; Linkesch, F.; Janetschko, R.; Machold, K.
Abstract : Objectives: Waiting times for first appointments are a major obstacle to timely Rheumatology care. In order to improve access, a cooperative of office based Rheumatologists established an immediate access network offering brief initial assessments for patients with musculoskeletal problems. Methods: Patients were assessed at presentation in the offices and followed up after 6 months. Data regarding demographics, diagnostic accuracy, clinical parameters such as pain levels, and care at baseline and after 6 months were analysed. Results: From October 2012 to March 2013 335 patients were assessed in the 6 cooperating practices during dedicated office hours (each office opening once a week for this service). 124 patients (38%) had a symptom duration less than 3 months, for rheumatoid arthritis (RA) patients this proportion was 42%. In the 271 patients available for reassessment after 6 months, initial suspected diagnosis was confirmed in 88%. Initial tentative diagnosis of RA (60 patients) was confirmed in 93%, of spondyloarthritis (46 patients) in 83%. At follow up, the visual analogue scale for pain in RA patients had significantly decreased from a median (IQR) of 70 (56 - 80) to a median (IQR) of 26 (20 - 42), for patients with spondyloarthritis from 50 (36 - 80) to 30 (20 - 40). Conclusions: The RAC resulted in a substantial waiting time reduction for rheumatology assessment. More than one third of the patients were seen before 3 months disease duration. Suspected diagnoses of inflammatory rheumatic diseases were correct in almost 90%. This initiative demonstrates the feasibility of a rapid access service and indicates high diagnostic accuracy in such a setting as well as the effectiveness of treatments recommended by the Rheumatologists. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4746